DIDACTIC POSSIBILITIES OF ENSURING THE EFFECTIVENESS OF PEDAGOGICAL ACTIVITY ON THE BASIS OF AN ACMEOLOGICAL APPROACH - Abdusamiyev Dilmurod Abdug’ani o’g’li (Journals Park Publishing, 2024)
In education, the search for effective pedagogical strategies has always been paramount. The acmeological approach, rooted in the study of human achievement and peak performance, offers a robust framework to enhance the effectiveness of teaching. Derived from the Greek word "acme," meaning peak or zenith, acmeology examines how individuals reach their highest levels of personal and professional development. When applied to pedagogy, this approach offers valuable insights into optimizing teaching methods, motivating students, and fostering an environment conducive to growth and excellence.
Keywords: acmeological approach, pedagogical effectiveness, didactic potential, continuous professional growth, self-reflection, goal setting, student-centered learning, individual potential, metacognitive skills.